Attenuation of cyclophosphamide-induced pulmonary toxicity in Swiss albino mice by naphthalimide-based organoselenium compound 2-(5-selenocyanatopentyl)-benzo[de]isoquinoline 1, 3-dione. (April 2015) - Ghosh, Prosenjit; Bhattacharjee, Arin; Basu, Abhishek; Singha Roy, Somnath; Bhattacharya, Sudin
Abstract Context: The widely used antineoplastic drug cyclophosphamide causes pulmonary toxicity by inducing oxidative stress. Selenium, a dietary micronutrient, has been found to protect various organs from oxidative injuries. Objective: This study was designed to investigate the protective efficacy of an organoselenium compound 2-(5-selenocyanato-pentyl)-benzo[de]isoquinoline 1, 3-dione against cyclophosphamide-induced pulmonary toxicity in Swiss albino mice. Materials and methods: Cyclophosphamide (25 mg/kg b.w.) was administered intraperitoneally for 10 d and the organoselenium compound (3 mg/kg b.w.) was given by oral gavage in concomitant and pretreatment schedules. Various biochemical parameters related to oxidative stress and antioxidant enzymes along with histology of lungs were evaluated to assess the effect of the test compound. Results: The oral LD50 of the test compound was more than 1000 mg/kg b.w. in Swiss albino mice. The test compound substantially ameliorated cyclophosphamide-induced pulmonary injury by reducing the levels of reactive oxygen species, reactive nitrogen species, and lipid peroxidation, respectively, by 14.88, 18.54, and 21.10% in concomitant treatment schedule and by 23.89, 35.73, and 30.76% in the pretreatment schedule as well as by restoring the level of reduced glutathione and activities of glutathione-S-transferase, superoxide dismutase, catalase, and glutathione peroxidase, respectively, by 36.88, 42.43, 38.0, 35.0, and 34.06% in the concomitant treatment schedule and by 66.02, 59.29, 57.23, 71.59, and 57.22% in the pretreatment schedule. The test compound also attenuated cyclophosphamide-induced histological alterations of lung tissue. Discussion and conclusion: The test compound emerged as an efficient antioxidant protecting lungs tissue from cyclophosphamide-induced injury.